Strategi Pemasaran dalam Meningkatkan Penjualan Sembako di PT. Avisha Berdasarkan Analisis SWOT - Elvina, Anastasia. S.; Somadi, Somadi (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
The background of the study is based on the company's sales and profit performance during the 2020-2024 period, amidst the increasingly tight competition in the staple food business, requiring a good and appropriate marketing strategy that is able to compete. Companies that are increasingly competitive in the staple food distribution sector require companies to have adaptive, innovative, and targeted marketing strategies. This study aims to analyze and disseminate the marketing strategies implemented by PT. Avisha in increasing staple food sales. The research method used is a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The analysis is conducted using a SWOT matrix to identify strengths, weaknesses, opportunities, and threats. The results of the study show that PT. Avisha, the company has a fairly strong position internally and has great opportunities in the external environment. The results of the IFAS analysis show that the main strengths of PT. Avisha lie in competitive prices during promotions, a variety of quality products, and a good distribution network, with a total score of 1.30. Meanwhile, weaknesses that still need to be improved include unstable sales, inefficient stock management, and dependence on discounts, with a total score of 1.20. On the other hand, the results of the EFAS analysis show that PT. Avisha has a great opportunity to increase sales of basic necessities through high market demand, online shopping trends, cooperation with MSMEs, and loyalty program innovation, with a total score of 1.50. However, the company also faces threats from price competition, rising prices of basic necessities, and changes in consumer habits, with a total score of 1.35. Overall, the company's position is in a condition that allows it to implement an aggressive strategy (Growth Strategy), especially through the use of internal strengths to seize external opportunities. The strategies developed include increasing digital promotion, optimizing distribution through collaboration with local partners, adjusting prices based on cost and market value, and developing customer loyalty programs. The strategy is expected to strengthen PT. Avisha's market position, increase marketing effectiveness and drive sustainable sales and profit growth.